The Influence of Start Up Entrepreneurs, Store Atmosphere and Service Quality on Green Marketing is Mediated by Consumer Satisfaction - Putri Nilam Sari; Ratna Handayati; Ruswaji; Puguh Cahyono (PT FORMOSA CENDEKIA GLOBAL, 2024)
Along with the development of the retail business, currently the retail business is no longer managed in a traditional way, but in a modern way. The rapid development in the business world can be seen from the rapid growth of modern shopping centers. All of this cannot be separated from the advantages offered by each shopping center. This research aims to determine the influence of start-up entrepreneurship, store atmosphere and service quality on green marketing mediated by consumer satisfaction. This type of research is a quantitative approach with a sample size of 132 consumers using purposive sampling techniques and the SEM-PLS analysis method with the SmartPLS Version 3.0 tool. Based on the research results, it is concluded that start-up entrepreneurship, store atmosphere and service quality have a positive and significant effect on green marketing and consumer satisfaction.